MANAGEMENT OF NASOPHARYNGEAL CANCER IN DR. ZAINOEL ABIDIN GENERAL HOSPITAL BANDA ACEH - Fadhlia; Ferawati; Irnawatii (TALENTA PUBLISHER, 2019)
Introduction: Most of the patients who are at an advanced or final stage of an illness usually comes from middle to low economic level. Right now, nasopharyngeal carcinoma management in Dr. Zainoel Abidin General Hospital Banda Aceh only has chemotherapy to treat patients. Actually patients need to also undergo radiotherapy treatment which unavailable in our hospital yet, so we will refer it to another hospital located in North Sumatera or Jakarta. Therefore, the Acehnese government is preparing to build an oncology center which includes radiotherapy, so that we can treat our patients here. Objective: The purpose of this research is to report management of NPC in Dr. Zainoel Abidin General Hospital Banda Aceh from January 2016 to October 2018. Method: Data was taken from medical records of patients diagnosed with NPC from January 2016 to October 2018. 73 patients was diagnosed with NPC and underwent chemotherapy. Result: There were 73 patients NPC, 44 (60.3%) patients are male (60.3%) and 29 patients are female (39.7%). The youngest patient is 13 years old and the oldest is 79 years old. Most common average age are between36-65 years old. The highest number is from Banda Aceh 10 patients. WHO histopathology classification reported that 26 (35.6%) patients with type I and type III as well, and 21 (28.8%) patients with type II. While 30 (41,1%) patients underwent chemotherapy for 6 cycles, 43 (58.9%) patients dropped out due to lack of living cost, long distance from hospital, or worsen of general condition. Conclusion: It was reported 73 patients NPC, 44 (60.3%) male and 29 (39.7%) female. The youngest 13 years old and the oldest 79 years old. Most common average age between 36-65 years old. The highest number was from Banda Aceh 10 patients, WHO histopathology classification reported 26 (35.6%) patients with type I and type III as well, and 21 (28.8%) patients with type II. While 30 (41.1%) patients underwent chemotherapy 6 cycles, 43 (58.9%) patients dropped out due to lack of the cost of. This study reported 4 (13.3%) patients who survived after underwent chemotherapy full dose with average range of 19-26 months.